2019
DOI: 10.1007/s00244-019-00627-8
|View full text |Cite
|
Sign up to set email alerts
|

Average Hourly Concentrations of Air Contaminants in Selected Urban, Town, and Rural Sites

Abstract: The inhabitants of cities, towns, and villages are exposed to different levels of air pollution, which also vary throughout the day. Information regarding episodes of poor and good air quality enables planning to mitigate the risks and maximize the benefits of spending time outdoors. In this work, an analysis was made of the state of air quality 2012–2016, using data gathered from automatic measuring stations located in five cities (> 50,000 inhabitants), five towns (5000–50,000 inhabitants), and five villages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
2
16
1
1
Order By: Relevance
“…The NO x concentration has been found to be higher at night than during the day [11], but the time at which the maximum concentration occurred has differed among studies [11,12]. For example, Robert Cichowicz found that the maximum values appeared at different times between 08:00 and 09:00 in five neighboring provinces in central Poland, Central Europe [13]. Changes in concentrations of atmospheric pollutants such as NO x during special periods (such as during the Beijing Olympics) or during atmospheric pollution events might vary significantly [14].…”
Section: Introductionmentioning
confidence: 99%
“…The NO x concentration has been found to be higher at night than during the day [11], but the time at which the maximum concentration occurred has differed among studies [11,12]. For example, Robert Cichowicz found that the maximum values appeared at different times between 08:00 and 09:00 in five neighboring provinces in central Poland, Central Europe [13]. Changes in concentrations of atmospheric pollutants such as NO x during special periods (such as during the Beijing Olympics) or during atmospheric pollution events might vary significantly [14].…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate the impact of emissions from road transport, which generates inter alia those three pollutants. However, ground-level ozone had a negative correlation to other analyzed pollutants, as its concentration is usually increasing in the afternoon, contrary to other air pollutants [6]. This could be a result of photochemical processes, affected by solar radiation and ambient temperature [21].…”
Section: Discussionmentioning
confidence: 89%
“…However, the O 3 concentrations had negative correlation with other pollutants. This was because in Poland the ground-level ozone reached the highest concentrations during early afternoon, resulting from occurrence of photo-chemical processes, while other pollutants had the highest concentrations in the morning, in the evening, or at night [6]. The calculated correlations were significant for the level 0.01, unless otherwise indicated in the tables.…”
Section: Source: Author'smentioning
confidence: 91%
See 1 more Smart Citation
“…High concentrations of pollutants generated by human activity occur especially in industrial areas and cities, as well as in other spaces such as agricultural or recreational areas. These pollutants directly and indirectly affect the air quality not only around the source of the pollution, but also in the surrounding area [2][3][4][5][6][7]. The main pollutants according to criteria established for the protection of human health and plant protection are particulate matter (PM10, PM2.5, and increasingly PM1.0) and gaseous pollutants such as benzene, nitrogen dioxide, sulfur dioxide, carbon monoxide, ozone, lead, arsenic, cadmium, nickel, and benzo (a) pyrene in PM10 dust, as well as hydrogen sulfide (H 2 S) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%